Kesulitan Guru dalam Penggunaan Media Pembelajaran Inovatif pada Pembelajaran IPS Kelas V SD Negeri 101873 Desa Baru Kec. Batang Kuis - Rizky Zulayha Siregar; Fadilla Tussyah Raini; Nur Hana; Auliya Sakinah; Khairunnisa Khairunnisa (Journal on Education, 2024)
Learning media is very important in order to maximize students' understanding of the material, but there are shortcomings for teachers when using innovative learning media. The aim of this research is to find out more about innovations in the use of learning media in social studies learning at SDN 101873 Desa Baru District. Quiz Bar. The methodology used in this research is qualitative descriptive research. Based on the results of observations and interview analysis, several challenges faced by teachers in implementing innovative learning media include the decreasing number of media used in learning models, the difficulty of teachers in evaluating innovative learning media, the lack of facilities in learning models. schools, and weakening government support for innovative teaching methods in schools.